Program Evaluation and Review Technique (PERT) in Agriculture (Indian Journal of Extension Education, 2018)
Under large scale agricultural projects, the managers are challenged with a task to coordinate various activities together. The process of planning incorporates a countless number of details to develop a realistic schedule and monitoring the progress of any project. The Indian agriculture over the years has evolved from simple technologies to complex establishment of projects which requires precise planning, coordination, implementation by the agricultural managers. These days, a huge amount of investment is sanction to develop agriculture for achieving higher productivity. To attain sustainable development, techniques must be used for careful allocation of resources and time management. There is a good scope of integration of the agro-food chain with the global market and keeping the importance of food safety, environmental issues and the growing demand for food. The policies made are directed to compete with the international quality and quantity and achieving sustainability goals. For this purpose, the farmers, policy makers and various stakeholders have to make complex choices in developing projects under a tight budget with a specific time frame.